Macro-micro-nano and mechanical characteristics of cement clinker-gypsum-slag-based hybrid geopolymer mortars: A novel approach for reducing the cost and carbon footprint - Tanyildizi, Harun; Kina, Ceren; Acik, Volkan (Elsevier, 2025)
This study introduced a new binder system that includes gypsum, clinker, and blast furnace slag (BFS) within an alkali-activated system to reduce carbon dioxide (CO2) emissions in cement production. The key innovation lies in separately using clinker and gypsum, eliminating the grinding process and combining them with alkali-activated BFS at varying replacement ratios. In this context, ten ambient temperature-cured (20 +/- 2 degrees C) alkali-activated mortars, blended with clinker, gypsum, and slag, were designed, along with one water-cured control mortar containing only clinker and gypsum. Their flow diameters, as well as the initial and final setting times, were evaluated to assess their fresh properties. The optimal replacement ratio of clinker and gypsum with BFS was determined by assessing the 3-and 28-day compressive strengths, bulk density, and dynamic modulus of elasticity. The results showed that the alkali-activated mortars having 20 wt % clinker + gypsum combined with 80 wt% BFS exhibited the highest 28-day strength of 69.26 MPa. The microstructural characteristics of these samples were identified through scanning electron microscopy/energy dispersive X-ray (SEM/EDX), Fourier Transform Infrared (FT-IR), and Thermogravimetric (TG) analysis. The molar ratios of Ca/Si and Na/Al in alkali-activated BFS mortar blended with 20 wt% clinker + gypsum indicated the predominance of calcium aluminosilicate hydrate (C-A-S-H) and a denser microstructure with an 11 % pore fraction. Nano-indentation tests revealed that the calcium/sodium aluminosilicate hydrate ((C, N)-A-S-H) volume fraction was 35 %. In contrast, no phases related to geopolymerization were observed in the alkali-activated clinker + gypsum mortar, which showed noticeable deep cracks and a 15 % pore fraction. The high-density calcium silicate hydrate (C-S-H) volume was 45 % for pure clinker + gypsum-based mortar and 30 % for the alkali-activated version. Furthermore, replacing 20 wt% clinker + gypsum achieved a CO2 capture of 32.16 % and a cost saving of 20.0 %. Consequently, using clinker + gypsum-without grinding process-into alkali-activated BFS in suitable proportions offered a promising alternative for improving eco-efficiency and sustainability.
Keywords: Clinker and gypsum; Alkali-activated slag; Strength and microstructure; Nanoindentation; CO (2) emission and cost